Keanekaragaman dan Kelimpahan Makrozoobentos di Sungai Naborsahan Kabupaten Toba Samosir Sumatera Utara - Melinda Sari Lubis; Mohammad Basyuni; Ani Suryanti (AQUACOASTMARINE, 2013)
This research described diversity and abundance of macrozoobenthos in Naborsahan River Toba Samosir Regency of North Sumatra. Macrozoobenthos sampling station consists of 3 stations using purposive random sampling method. Physical and chemical parameters were measured as temperature, currents, depth, brightness, turbidity, organic content on C-substrate, pH, DO, and BOD5. Macrozoobenthos obtained 5 phylum, i.e. Annelida, Arthropoda, Nemertea, molluscs and Platyhelminthes which were divided into 26 genera. First station had a value diversity index (H') of 2,25 with a high of 11 genera. Tryonia genera had the highest value abundance of 14.430 ind/m2 that found at third station.Keywords: Diversity, Abundance, Macrozoobenthos, Naborsahan.